Genetic polymorphisms of long noncoding RNA RP11‐37B2.1 associate with susceptibility of tuberculosis and adverse events of antituberculosis drugs in west China - Song, Jiajia (J Clin Lab Anal, 2019)
BACKGROUND: Little knowledge about the biological functions of RP11‐37B2.1, a newly defined long noncoding RNA (lncRNA) molecule, is currently available. Previous studies have shown rs160441, located in the RP11‐37B2.1 gene, is significantly associated with tuberculosis (TB) in a Ghanaian and the Gambian populations. METHODS: We investigated the influence of single‐nucleotide polymorphisms (SNPs) within lncRNA RP11‐37B2.1 on the risk of TB and the possible correlation with adverse drug reactions (ADRs) from TB treatment in a Western Chinese population. Four SNPs within lncRNA RP11‐37B2.1 were genotyped in 554 TB cases and 561 healthy subjects using the improved multiplex ligation detection reaction method, and the patients were followed up monthly to monitor the development of ADRs. RESULTS: No significant association between the SNPs of lncRNA RP11‐37B2.1 and TB susceptibility was observed (all P > 0.05). Surprisingly, significant association was observed between two SNPs (rs218916 and rs160441) and thrombocytopenia development during anti‐TB therapy under the dominant model (P = 0.003 and 0.014, respectively). CONCLUSIONS: Our findings firstly exhibit that rs218916 and rs160441 within lncRNA RP11‐37B2.1 significantly associate with the occurrence of thrombocytopenia and suggest RP11‐37B2.1 genetic variants are potential biosignatures for thrombocytopenia during anti‐TB treatment.